Pendapatan Usahatani Cabai Merah Besar Di Desa Langi Kecamatan Bontocani Kabupaten Bone - Zulmiah; Sri Mardiyati; Muh. Ikmal Saleh (KaliAgri Journal, 2023)
One type of remarkable horticultural plant in Indonesia was red chilies. Red chili (Capsicum annuum L.) was one of vegetable commodity that people need in daily life. Red chili also contains beneficial nutrients for human health such as vitamin A, Vitamin C, carotene, iron, potassium, calcium and phosphorus. Langi village was one of the vilages in Bontocani District, Bone Regency where most of the people cultivated red chili. The most common problem encountered was the production fluctuacions caused by pests and diseases as well as short productive plant age. So it was necessary to carry out activities to increase the income of red chili farming for it was main commodity of the villagers. This study aimed to determine the income of red chili farming in the research location. The samping technique used in this study was probability sampling as many as 30 red chili farmer respondents involved. Data were collected by observation, interview and documentation. Data analysis used was income analysis, analysis of the Coeficient of Variation (CV). The results showed the production level of red chili was classified as high, with an average annual production of 7115.87 kg/ha. The total revenue was Rp. 151,093,618.81 and the income earned was Rp. 138,782,020.31.